A AGRESSÃO COMO FORMA DE DESENGAJAMENTO MORAL NO TRÂNSITO DO MUNICÍPIO DE SÃO LUÍS DO ESTADO DO MARANHÃO. - OLIVEIRA, Suzana Maria de (2019)
The main objective of this dissertation was as follows: the notion of a public transit space and the streets of a metropolis, in this case, the capital of São Luis do Maranhão, based on the moral disengagement theory of Albert Bandura (2015; 2008). The aforementioned theory is one of the basic constructs of the Cognitive Social Theory formulated by Canadian psychologist Bandura, neither an ignored person nor the moral parameters themselves in order to act reproachfully through a set of eight justifying psychosocial mechanisms, regardless of the social context, an example of the aggression resulting from a collision between two vehicles. In addition, action may be a risk factor for social change, social repercussions can result in homicide from, for example, driving behind-the-scenes, which justifies its study. This is a bibliographical research in Psychology of descriptive characteristics, with interdisciplinary characteristics by complementing knowledge in Social Sciences, by authors such as Roberto DaMatta (2010; 1997), Georg Simmel (2006; 1976) and Norbert Elias (1994; 1993). The approach thus adopted is interdisciplinary to better understand reality in view of the interest in the study of a complex discipline that exceeds the scope of a discipline or specialty. The choice for the interdisciplinary approach also led to an emphasis on the interactionist perspective on morality. A study of this dissertation is currently showing studies pointing, directly or indirectly, to the phenomenon of aggression human in the traffic, with a view intervention projects, particularly in the metropolises. It was concluded that aggression is multifactorial, however, as Bandura Theoretic constructions present subsidies for a better understanding of the phenomenon in question.